Identification of Barriers and Challenges of Virtual Education at Macro, Meso, and Micro Levels - Mozaffari Khosravi, Mahmoud; Zarghami Hamrah, Saeed; Mahmoudi, Mahdi (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study was conducted with the aim of examining the indicators of barriers and challenges of virtual education at macro, meso, and micro levels. Methods and Materials: The method employed in this research is a mixed-methods approach. In the qualitative section, documents from the Ministry of Education of the Islamic Republic of Iran, including the "Fundamental Theoretical Foundations for Formal and Public Education Transformation," the "Fundamental Transformation Document of Education," and the "National Curriculum Document," were analyzed. In the quantitative section, two non-random sampling methods were used: non-probability sampling and snowball sampling, which is a non-probability sampling method commonly used in sociology and statistical research. The research population consisted of 150 students from Farhangian University and 10 faculty members from the same institution. Interviews were conducted based on a competency model, and the appropriate tool was developed and implemented after determining its validity and reliability using Cronbach's alpha (α = 0.92). Findings: Based on the findings, 150 digital teacher competencies were categorized into 9 sections, which were further divided into three main areas: curriculum design, barriers to virtual education, and the quality of virtual teaching. The challenges identified in the study were categorized at macro, meso, and micro levels, and the results are applicable for identifying the indicators of barriers and challenges in virtual education. Conclusion: The results of the study indicate that, at the macro level, poor policy-making is the primary issue, at the meso level, budget disruptions are prominent, and at the micro level, students, more than parents, teachers, and professors, believe that the barriers and challenges of virtual education are greater than those of in-person education.